Cost–utility analysis of once-daily versus twice-daily inhaled corticosteroid dosing for maintenance treatment of asthma in pediatric patients (2020)
Objective: Suboptimal adherence to inhaled corticosteroids (ICs) is an important cause of poor asthma control in pediatric patients. Among the factors that can be most easily changed for enhancing adherence to ICs is a reduction in the dosing frequency, from twice-daily dosing to once-daily dosing. However, no previous studies have reported an economic evaluation comparing once-daily versus twice-daily IC dosing for pediatric asthma. The aim of this study was to compare the cost-effectiveness of once-daily versus twice-daily IC dosing for maintenance treatment of asthma in pediatric patients. Methods: A Markov-type model was developed in order to estimate costs and health outcomes of a simulated cohort of pediatric patients with persistent asthma treated over a 12-month period. Effectiveness parameters were obtained from a systematic review of the literature. Cost data were obtained from official databases provided by the Colombian Ministry of Health. The main outcome was the variable “quality-adjusted life-years” (QALYs). Results: For the base-case analysis, the model showed that compared with twice-daily dosing, once-daily dosing strategy involved lower costs (US$1529.3 versus $1709.1 average cost per patient over 12 months) and the greatest gain in QALYs (0.8284 versus 0.8084 QALYs on average per patient over 12 months), resulting in once-daily dosing strategy being considered dominant. Conclusions: This study shows that compared with twice-daily dosing, once-daily IC dosing for treating pediatric patients with persistent asthma is the dominant strategy because it involves a greater gain in QALYs at lower total treatment cost.